Architecting Nb‐TiO2−x/(Ti0.9Nb0.1)3C2Tx MXene Nanohybrid Anode for High‐Performance Lithium‐Ion Batteries. Issue 3 (11th December 2021) - Dai, Zhiqiang; Cao, Jin; Song, Feng; Zhang, Dongdong; Qin, Jiaqian; Zhang, Xinyu
Abstract: MXene‐based materials with excellent conductivity and stability features have attracted worldwide attention as anode of lithium‐ion batteries (LIBs), while the serious stacking issue and low capacity still hinder its further development in the field of energy storage. In this work, a nanohybrid architecture (Nb‐TiO2− x /MXene) is prepared with Nb‐TiO2− x particles conformally coated on the (Ti0.9 Nb0.1 )3 C2 T x MXene via a facile annealing method, which delivers a high specific capacity of 279.2 mAh g −1 at the current density of 0.1 A g −1 and a superior capacity retention of 91.5% after 2000 cycle at 1 A g −1 as the anode material of LIBs. Importantly, the (Ti0.9 Nb0.1 )3 C2 T x MXene layers provide sufficient active sites and open pathways as well as structural support for the reversible Li + insertion/extraction, and the Nb‐TiO2− x particles enable reversible and fast Li + diffusion and storage, thus leading to high‐performance and durable anode materials. This work offers a guidance for the elaborate design of MXene‐based nanostructured electrodes toward advanced energy storage devices. Abstract : Nanohybrid architecture (Nb‐TiO2− x /MXene) is prepared with Nb‐TiO2− x particles conformally coated on the (Ti0.9 Nb0.1 )3 C2 MXene via a facile annealing method, which delivers a high specific capacity of 279.2 mAh g −1 at the current density of 0.1 A g −1 and a superior capacity retention of 91.5% after 2000 cycle at 1 A g −1 as the anode material of lithium‐ion batteries.